PENGARUH KONSENTRASI PUPUK ORGANIK CAIR DARI BEBERAPA JENIS BATANG PISANG TERHADAP PERTUMBUHAN HASIL SAMBUNG PUCUK BIBIT ALPUKAT (Persea americana Mill) - Idris, M Setiawan; Susiyanti, Susiyanti; Fatmawaty, Andi Apriany; Firnia, Dewi; Lizansari, Kirana Nugrahayu (Fakultas Pertanian Universitas Mataram, 2024)
Avocado production in Banten Province fluctuates due to suboptimal nutrient provision. This study used local variety YM avocado seedlings from Lebak Banten which were propagated by grafting. This study aims to determine the effect of liquid organic fertilizer (LOF) concentration from several types of banana stems on the growth of grafted avocado seedlings (Persea americana Mill.). This study used a factorial Randomized Block Design (RBD) consisting of 4 concentration levels: 0, 150, 300, and 450 ml/l and 3 types of banana stems: nangka banana stems, kepok banana stems, muli banana stems. Based on the results of the study, the administration of LOF with a concentration of 300 ml/l gave the best effect on the parameters of seedling height increase, leaf number increase and leaf greenness index. A concentration of 450 ml/l gave the best effect on the parameters of seedling height increase, stem diameter increase, leaf length increase and leaf width increase. While the type of LOF from nangka banana stems gave the best effect on seedling height increase. There is an interaction between the concentration and type of banana stem on the parameters of the comparison of the length and width of avocado plant leaves.